ANALYSIS OF INDONESIAN EDIBLE BIRD'S NEST EXPORTS TO HONG KONG IN 2018 – 2022 - Halkam, Hamka (Journal of Social Political Sciences, 2024)
This study aims to analyze the Indonesian bird’s nest export to Hong Kong. Exporting is the act of selling goods and services produced by one country to buyers in another country. Importing is the act of purchasing goods and services produced by another country. Exporting and importing form international trade. According to the Export-base Theory, exporting can be a major factor in the economic growth of a country. Exporting leads to an increase in the inflow of money into a country, which in turn stimulates economic growth. Indonesia provides 80% of the world's edible bird’s nest needs. From 2018 to 2022, Hong Kong was the largest importer of Indonesian edible bird’s nest. During the period, Indonesian edible bird’s nest export to Hong Kong was 711,2 tons annually or approximately 51,8% of Indonesian edible bird’s nest total export volume. This research used qualitative approach which data collection library research; secondary data. The data is analyzed by comparing the volume and value of Hong Kong’s edible bird’s nest export and import and the volume and value of Indonesian edible bird's nest export to this country. The results showed that Indonesian bird’s nest export to Hong Kong was increased in term of export volume. However, it was decreased in terms of export value. Indonesia has become the largest contributor for Hong Kong’s edible bird’s nest import during the periode.